PRODUK GRAF FUZZY INTUITIONISTIC - Zumiafia Ross Yana Ningrum; Lucia Ratnasari (MATEMATIKA FSM, UNDIP, 2012)
An intuitionistic fuzzy graph G:V,E consist of a couples of node sets V and set of edges E which the sum of degree membership and degree non membership each of nodes and each of edges in closed interval [0,1], the degree membership each of edges is less than or equal with the minimum of degree membership each nodes of incident, and degree non membership each of edges is less than or equal with the maximum degree non membership each nodes of incident. Product fuzzy graph was defined by Dr. V. Ramaswamy and Poornima B. Product fuzzy graph is fuzzy graph, where the degree membership each of edges is less than or equal with product of the between degree of membership each nodes of incident. In this paper we study the definitions of product intuitionistic fuzzy graph, product intuitionistic fuzzy graph complete, further discussion about the complement of product intuitionistic fuzzy graph, join of product intuitionistic fuzzy graph and multiplication of product intuitionistic fuzzy graph and their characteristics.